The effectiveness of advertising campaign in encouraging students and staff of UiTM to promote the industry-university collaboration through Industry, Community & Alumni Network (ICAN) / Muhammad Azzam Khamsani - Khamsani, Muhammad Azzam (Faculty of Art and Design, 2013)
knowledge economy has intensified the need for strategic partnerships that go outside the traditional funding of different research projects. World-class research universities are at the front line of pioneering such partnerships. They are designed to run longer, invest more, look farther ahead and polish the competitiveness of companies, universities and regions. In short, they transform the role of the research university for the 21st century, put in it as a vital centre of efficiency to help tackle social challenges and drive economic growth.But it’s a big jump. It requires each side to engage far beyond the conventional exchange of research for funding. When they work well, strategic partnerships merge the discovery-driven culture of the university with the innovation driven environment of the company. But to make the chemistry work, each side must overcome the cultural and communications divide that tends to affect industry- university partnerships of all types and undercut their potential